Classification of Industrial Relations Disputes Settlement in Indonesia: Is it Necessary? - Desak Putu Dewi Kasih; Made Suksma Prijandhini Devi Salain; Kadek Agus Sudiarawan; Putri Triari Dwijayanthi; Dewa Ayu Dian Sawitri; Alvyn Chaisar Perwira Nanggala Pratama (Hasanuddin Law Review, 2022)
This study aimed to examine the effect of the disputes classification in the industrial settlement system, comparing arrangements according to the perspective of the International Labor Organization, China, Japan, and Kazakhstan, and trying to find the ideal concept of the type of industrial dispute to apply in Indonesia. This research is normative legal research. The approaches used in this study were the statutory approach, conceptual approach, fact approach, and comparative approach. The results revealed that the classification of disputes in the industrial relations settlement system in Indonesia has an impact on the difficulty of the parties in classifying their disputes. Comparative studies were conducted to determine the classification of disputes in international law as well as in China, Japan, and Kazakhstan. The ideal concept that can be offered to Indonesia is the simplification or elimination of the classification of industrial relations to provide dispute resolution by applying the principles of fast, precise, fair, and inexpensive methods.